Isolation and Characterization of Caffeine-Degrading Bacteria from Coffee Plantation Areas in Malaysia - Dullah, Elvina Clarie; Farida Asras, Mohd Fazli (UI Scholars Hub, 2023)
Decaffeination by microbial degradation is currently the most optimal and low-cost approach, involving only microbial cells and/or their enzymes. The bacterium was characterized using a series of biochemical tests. Positive results were obtained from carbohydrate fermentation, citrate utilization, and catalase tests, while negative results were obtained from Voges-Proskauer (VP) and indole tests. Three different caffeine concentrations of 0.25%, 0.4%, and 2% were tested and measured through Gas Chromatography-Mass Spectrophotometry (GC-MS) analysis. The highest caffeine reduction (89.25%) was found when 0.25% caffeine was used in the media. Only a small amount of caffeine was reduced to 0.4% and 2%, with 34.78% and 46.16%, respectively. Under microscopic observation, the shape of the isolated bacteria was rod bacilli and was stained with a pink color, which indicates Gram-negative bacteria. Comparing the results with previous research and observing the color of the pure culture, which revealed a yellow color, bacteria isolated from the coffee plantation area can be concluded to be a partially identified Pseudomonas sp.